THE EFFECT OF THIRD PARTY FUNDS, NON-PERFORMING FINANCING AND OPERATING EXPENSES OF OPERATING INCOME ON FINANCIAL PERFORMANCE: (Empirical Study of Sharia Commercial Banks for the Period 2016-2020) - Heranita; R. Mohd. Zamzami (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
This study intends to investigate the influence of Third Party Funds, Non-Performing Finance (NPF), and Operating Income (BOPO) on Financial Performance, as measured by Return On Assets (ROA). This study's population consists of Sharia Commercial Banks registered between 2016 and 2020 with the Financial Services Authority (OJK). This study drew samples from seven Islamic commercial banks using a method of purposive sampling. Obtained sample data as much as 35 data. The data utilized for this study are secondary data. This type of research is causal associative with a quantitative approach method. Multiple linear regression analysis with a 5% significance level is the technique employed. This research is processed using Eviews 12 software. The results show that (1) Third Party Funds have a significant effect on Financial Performance (2) Non-performing Financing Results have no effect on Financial Performance, (3) Operating Expenses Operating Income has a significant effect on Financial Performance. (4) Third Party Funds, Non-performing Financing, and BOPO have a joint influence on Financial Performance. In the coefficient of determination of the variable TPF, Non-performing Financing and BOPO have an influence of 72% on Financial Performance while 28% is influenced by other factors beyond this study.